2009
DOI: 10.1039/b909872k
|View full text |Cite
|
Sign up to set email alerts
|

Structural changes of noble metal catalysts during ignition and extinction of the partial oxidation of methane studied by advanced QEXAFS techniques

Abstract: The dynamics of the ignition and extinction of the catalytic partial oxidation (CPO) of methane to hydrogen and carbon monoxide over Pt-Rh/Al(2)O(3) and Pt/Al(2)O(3) were studied in the subsecond timescale using quick-EXAFS with a novel cam-driven X-ray monochromator employing Si(111) and Si(311) crystals. The experiments were performed under reaction conditions in a small fixed-bed capillary reactor. For the first time XAS data were taken with this QEXAFS technique with a Si(311) crystal that opens the energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 65 publications
1
44
0
1
Order By: Relevance
“…Operando XAS has allowed analyzing dynamic changes during the oscillatory oxidation of CO71 or partial oxidation of CH 4 72 uncovering in both cases strong changes in the oxidation state. Time resolution in the ms regime can be achieved using both dispersive EXAFS (DEXAFS, Turbo‐XAS)73 and quick‐EXAFS (including a continuously scanning monochromator) 74. Using an X‐ray camera even spatially and temporally resolved structure changes could be recorded, as exemplified in Figure 7.…”
Section: Advancing the Characterization Methods: Following Dynamics mentioning
confidence: 99%
“…Operando XAS has allowed analyzing dynamic changes during the oscillatory oxidation of CO71 or partial oxidation of CH 4 72 uncovering in both cases strong changes in the oxidation state. Time resolution in the ms regime can be achieved using both dispersive EXAFS (DEXAFS, Turbo‐XAS)73 and quick‐EXAFS (including a continuously scanning monochromator) 74. Using an X‐ray camera even spatially and temporally resolved structure changes could be recorded, as exemplified in Figure 7.…”
Section: Advancing the Characterization Methods: Following Dynamics mentioning
confidence: 99%
“…Of these, quick X-ray absorption fine-structure (XAFS) spectroscopy is one of the most useful methods to observe AuNP formation process in situ because the chemical state and the structure of AuNP can be analyzed from the spectra. [15,16,17] Recently, Polte et al observed the formation process of AuNPs with citric acid by coupled in situ XANES and small-angle X-ray scattering (SAXS) spectroscopy. [18] This helped to describe the mechanism of nanoparticle formation, which was found to comprise different steps of particle growth via both the coalescence of nuclei and further monomer attachment.…”
Section: Junya Ohyamamentioning
confidence: 99%
“…Next, in situ EDXRD measurements did not point to any structural changes or to dissolution of the Bi 2 O 3 precursor, thereby suggesting a solid-solid transformation as the most plausible mechanism. To acquire more detailed insight into the liquid phase of the hydrothermal system, we performed in situ QEXAFS (quick-scanning extended X-ray absorption spectroscopy) investigations [274] at the Bi-L 3 edge. They indicated a solubility of approximately 0.4 mol % Bi at 160 8C, thereby pointing to a slower reaction process.…”
Section: Reviews 846mentioning
confidence: 99%